The Influence of Internal And External Factors On The Entrepreneurial Interest of Fashion Design Students At Pencawan Vocational School, Medan - Angel Angel; Tri Utari Ismayuni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of internal and external factors on the entrepreneurial interest of Fashion Design students at Pencawan Vocational High School, Medan. The study used a quantitative approach with multiple linear regression. The research sample was 32 grade XI students selected through total sampling. The research instrument was a questionnaire whose validity and reliability had been tested. The results showed that internal factors contributed positively but not significantly to entrepreneurial interest (t = 1.121; Sig. = 0.272), while external factors had a significant influence (t = 2.751; Sig. = 0.010). Simultaneous tests showed that both factors together had a significant influence on entrepreneurial interest (F = 7.862; Sig. = 0.002), with external factors being more dominant (β = 0.704) than internal factors (β = 0.270). Thus, family, school, and environmental support play a greater role in increasing students' entrepreneurial interest, while internal factors function as supporting capital.